Gender Inequality in Education and the Reasons of its Variation Across Assam, India - Basumatary, Roselin; Das, Manjit (Arthshastra Indian Journal of Economics & Research, 2018)
Gender inequality in education is the inequality in education between males and females. Several studies upon gender inequality in education showed that it acts as an obstacle to development. The study aimed to find out the extent of gender inequality in education across Assam, the extent of gender inequality in education across Assam in different age groups, and the reasons of variation of gender inequality in Assam. To examine the extent of gender inequality in education across Assam, gender parity index (GPI) with respect to literacy rate (LR) in the period from 1971 to 2011 and education for all development index (EDI) for the years 2012-2013 and 2013-2014 were calculated. Calculated GPI of LR showed that in all the districts of Assam and Assam as a whole, gender inequality in education where females lag behind males existed in the period. EDI values for the districts for which it were calculated were not found to be satisfactory for both the years. However, on comparing the EDI values of the state as a whole for the years 2012 - 2013 and 2013 - 2014, it was found that the EDI values increased, showing an improvement in terms of access, quality, and gender gap. To find out the gender inequality in education in different age groups, gender gap (GG) of illiteracy rate (ILR) for the year 2011 was calculated for the districts of Assam. It is found that, in all the age groups, that is, 7-14, 15-19, 20-24, 25-29, 30-34, 35-59, 60, above (60+), and age not stated (ANS), female ILR surpassed male ILR in majority of the districts and in the state. Moreover, in the state as a whole and in majority of the districts, the gender inequality in ILR increased with the higher age groups, that is, from 7-14 up to 60+. To find out the reasons of variation in gender inequality in education in Assam, cross section data for 2011 upon GPI of LR, percentage of scheduled caste (SC) and scheduled tribe (ST), percentage of poverty, per capita gross district domestic product (PCGDDP), population size, percentage of rural population, percentages of Hindus, Muslims, Christians, Sikhs, Jains and Other persuasions population were used in regression analysis. It was found that the impact of poverty on GPI of LR was significantly negative. It was also found that the impact of Muslims, Sikhs, Jains, and others (excluding Hindus, Christians, Sikhs, Jains, Buddhists, and religion not stated) on GPI of LR was significantly positive, while the impact of Christians on GPI of LR was significantly negative.